Insects in the instructional texts of the “philosophical travels” in the XVIII Century - Almeida, Argus Vasconcelos de; Albuquerque, Auristela Correia de; Oliveira, Marco Aurélio Paes de (SITIENTIBUS série Ciências Biológicas, 2010)
The purpose of this paper is to analyze how insects were conceived in the instructional texts of the “philosophical travels”. After reviewing the historical literature about scientific excursions undertaken in the eighteenth century in colonies of the Portuguese Empire, it was possible to identify concepts about the class Insecta in terms of biology, systematic, external morphology, collection organization and preparation methods held at the time. It was also possible to notice a conceptual evolution about insects which were considered “imperfect beings” in a first moment and later as “nature ministers”. Those instructions were followed in many Brazilian regions, as an example, the naturalist Manoel Arruda da Camara, Vandelli’s disciple, has carried out several scientific excursions in the Northeast region, in which he identified, collected and drew several groups of insects.